Investigating the complex story of one ditch-A multidisciplinary study of ditch infill provides insight into the spatial organisation within the oppidum of Bibracte (Burgundy, France) - Goláňová, Petra; Hajnalová, Mária; Lisá, Lenka; Milo, Peter; Petr, Libor; Fránková, Markéta; Kysela, Jan; Flammer, Patrik G; Kočárová, Romana; Barta, Peter (PLoS One, 2020)
Seemingly empty spaces in various archaeological settings have left many unanswered questions. This paper focuses on the appearance, maintenance and possible function of a large empty area situated at the summit plateau of the Iron Age oppidum Bibracte in France. Multidisciplinary research of the infill of the ditch that delimited this area in the 1st century BC has provided evidence on the primary function and the formation processes of the structure itself, and for the reconstruction of the appearance, maintenance and function of the area it enclosed. The results allow us to gain insight into a variety of topics, including the role of trees, hygiene measures and waste management strategies at this urbanised hilltop centre. This paper demonstrates that multi-proxy analyses provide detailed insight into the function of archaeological features in a local environmental context and the potential of such approaches in archaeology.
Keywords: Trees; Humans; Urbanization; archeologie; stromy; lidé; rozsivky; dějiny starověku; Francie; France; Diatoms; radioaktivní datování; History, Ancient; Archaeology; urbanizace; Geological Phenomena; geologické sedimenty; Radiometric Dating; nakládání s odpady; Waste Management; geologické jevy; Geologic Sediments